Fostering a frugal living: Examining mental accounting and green consumption among Indonesian generation Z - Tsabitah, Reyva Putri; Amelia, Vanesia; Lidiyawati, Lidiyawati (Edelweiss Applied Science and Technology, 2026)
Frugal living is becoming a more common lifestyle choice among Indonesia’s Generation Z (17–28 years old), largely due to rising financial pressures and a growing concern for environmental sustainability. This study explores how Mental Accounting and Green Consumption influence their tendency to live more frugally, especially through deliberate financial decisions and consumption habits grounded in ethical and environmental considerations. Using a quantitative method, data were gathered from 300 respondents through an online survey. Initial statistical tests were conducted with SPSS 23, and the structural model was examined using AMOS Graphics 25. The results strongly support the proposed relationships. Mental Accounting helps individuals organize and manage their finances with greater awareness, while Green Consumption encourages them to make choices that are responsible and environmentally sound. These two factors together play a meaningful role in shaping frugal living behaviors among Indonesian Gen Z. The study concludes that financial awareness and sustainability-oriented values play an important role in shaping cost-conscious and environmentally responsible lifestyles. Practically, these findings highlight the importance of promoting financial literacy and sustainable consumption awareness to encourage frugal living among younger generations.